The Influence of Job Characteristics and Individual Characteristics on Organizational Commitment and Implications on Job Satisfaction - Yohana Jesika Lujunai; Survival; Mulyono (Optima Science, 2025)
The purpose of the study was to analyze the influence of job characteristics and individual characteristics on organizational commitment and their implications for job satisfaction. This study is a positivist study, with an explanatory or explanatory type of research. This study uses a quantitative approach because the data that will be used to analyze the relationship between variables is expressed in numbers or numerical scales. The population in this study includes all employees working at PT. Best Profit Futures Malang branch office totaling 131 employees. To measure the sample size to be studied, the researcher used the Slovin formula, which was 57 employees. The statistical data analysis technique through Path Analysis used in this study is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS application. The results showed that job characteristics have a significant positive effect on job satisfaction. Individual characteristics do not have a significant positive effect on job satisfaction. Job characteristics have a significant positive effect on organizational commitment. Individual characteristics have a significant positive effect on organizational commitment. Organizational commitment has a significant positive effect on job satisfaction. Job characteristics have an effect on job satisfaction mediated by organizational commitment. Individual characteristics have an effect on job satisfaction mediated by organizational commitment.